2009
DOI: 10.1002/micr.20626
|View full text |Cite
|
Sign up to set email alerts
|

Sural perforator flap: Assessment of the posterior calf region as donor site for a free fasciocutaneous flap

Abstract: Three kinds of free fasciocutaneous flap from the posterior calf region have been described in the literature: the medial sural perforator flap, the lateral sural perforator flap, and the traditional posterior calf fasciocutaneous flap that is supplied by superficial cutaneous vessels. Moreover, it has been reported that superficial cutaneous vessels are of a suitable size for microanastomosis when deep musculocutaneous perforators are absent or relatively tiny. To establish a safe technique for free fasciocut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…It relies on the intrinsic and extrinsic neurocutaneous or venocutaneous vascular supply that accompanies the sural nerve. The blood supply of the flap comes from the superficial sural artery, perforators from the posterior tibial artery, and perforators from the peroneal artery . These perforators connect with each other in the subcutaneous plane, forming a longitudinal chain‐linked vascular plexus along the course of the sural nerve .…”
Section: Discussionmentioning
confidence: 99%
“…It relies on the intrinsic and extrinsic neurocutaneous or venocutaneous vascular supply that accompanies the sural nerve. The blood supply of the flap comes from the superficial sural artery, perforators from the posterior tibial artery, and perforators from the peroneal artery . These perforators connect with each other in the subcutaneous plane, forming a longitudinal chain‐linked vascular plexus along the course of the sural nerve .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the diameter of the superficial lateral sural artery was found to be 0.5 mm on average, whereas the superficial median artery had a diameter of 1 mm. In a recent study by Shimizu et al11 superficial median and lateral sural arteries with diameters of 0.8 to 2.7 mm (median) and 0.4 to 2.5 mm (lateral) were found in 12 formalin‐ fixed legs, but in 3 specimens, no suitable superficial system was present at all. Walton et al7, 12 dissected 11 cadaver legs and described the superficial sural artery as a direct cutaneous branch developing from the popliteal artery in 50% and from the deep lateral sural artery in 45% of the specimens.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, the major perforator of the medial sural artery is easier to identify than the perforators of other flaps, thus enabling a rather safe and rapid dissection between the deep fascia and the medial gastrocnemius muscle. [14][15][16] Under these circumstances, the surgeon is not only required to cover an existing tissue defect but also to achieve a good-quality and natural-looking reconstructed site. Many factors affect the choice of the flap used for a particular patient, and the reconstructive procedure should be chosen depending on the characteristics of the defects.…”
Section: Discussionmentioning
confidence: 99%
“…12,[14][15][16][17] The ALT flap, first described by Song et al in 1984, is a perforator skin flap that leaves the muscle essentially intact, thereby minimizing donor site morbidity. The use of ALT flaps also allows simultaneous flap harvest and recipient site preparation, thus allowing a shorter surgical period, and enabling the patient to rest in a supine position during the procedure.…”
Section: Discussionmentioning
confidence: 99%